A 1.8 to 4 GHz inductor-less highly linear CMOS LNA for wire-less receivers - Luan; Nguyen Huu Tho (Journal of Military Science and Technology, 2021)
This paper presents an inductor-less wide-band highly linear low-noise amplifier (LNA) for wire-less receivers. The inductor-less LNA consists of a complementary current-reuse common source ampliﬁer combined with a low-current active feedback to obtain wide range input impedance matching and low noise figure. In our LNA, a degeneration resistor is utilized to improve linearity of the LNA. Furthermore, we designed a bypass mode for the LNA to extend the range of its applications. The proposed LNA is implemented in 28 nm CMOS process. It has a gain of 14.9 dB and a bandwidth of 2.2 GHz. The noise ﬁgure (NF) is 1.95 dB and the third-order input intercept point (IIP3) is 24.8 dBm at 2.3 GHz. It consumes 17.2 mW at a 0.9-V supply and has an area of 0.011 mm2.